Analisis Dampak Pandemi Covid-19 Terhadap Pelaksanaan Program UKS Pada Sekolah Dasar Di Kabupaten MUsi Rawas - Deasi Novia; Misnaniarti Misnaniarti; Rostika Flora; Risnawati Tanjung (Jurnal Kesehatan Komunitas, 2021)
Coronavirus Disease 2019 (COVID-19) pandemic changes the order of life in society, so a clean and healthy lifestyle or Perilaku Hidup Bersih dan Sehat (PHBS) has to be implemented in daily life to prevent COVID-19 deployment. One of the efforts to adapt to a clean and healthy lifestyle is education. School Health or well know in Indonesia as Usaha Kesehatan Sekolah (UKS) is expected able to become a platform for improving student’s skills and capability regarding designing a clean and healthy lifestyle. PHBS is a key to cut off COVID-19 chain deployment. The research has a goal to analyze the pandemic’s effect COVID-19 pandemic towards UKS implementation in elementary school in Tuah Negeri District in Musi Rawas Regency, Sumatera Selatan Province. It was explorative qualitative research which is conducted in five different elementary schools in the District of Tuah Negeri, Musi Rawas Regency, Sumatera Selatan Province. The informants are Head of Air Beliti health care, Person in Charge of UKS program from health care, Principal, Person in Charge of UKS from elementary school, and several elementary school students. The data analysis used Miles and Huberman's theory. The steps are reduction, presentation, verification. Testing of validity is processed through the Triangulation method. The result found conduction of UKS Triassic in elementary school in Tuah Negeri District during the COVID-19 pandemic was still implemented. Health education tends to emphasize more on PHBS counseling health protocol. Health service is limited on nutrition status observation through weight and height measurement. The immunization program for a student was still held by health care but did not achieve the target. In school environment’s coaching, in general, every school has provided handwashing facilities and infrastructure in each class. Implementation of UKS during the pandemic of COVID-19 in elementary school under the administration of Tuah Negeri Regency, Musi Rawas Regency, Sumatera Selatan Province is still on conduction. But not all the program has an optimal outcome. Because there was a limitation due to the pandemic situation. It showed by the total number of students who attend the school physically has to be reduced.